Improving nitrogen use efficiency of mixed fertilizers using clinoptilolite zeolite - Rabai Nasip, Krystle Amanda (2013)
According to Wu and Liu (2008), up to 70% of N, 90% of P, and 70% of K are lost to the environment and not available for plant uptake. This leads to economic losses and causes serious environmental pollution. Blending mixed fertilizers with clinoptilolite zeolite where the zeolite acts as excellent carrier regulator and stabilizes mineral fertilizers could be an alternative way of formulating desired fertilizers in agriculture. An incubation experiment was carried out to compare the effects of different ratios of mixed fertilizers amended with clinoptilolite zeolite on ammonia (NH3) volatilization, soil exchangeable ammonium (NH4 +) and available nitrate (NO3 -) contents on a fine, loamy, siliceous, hyperthermic, Typic Paleudults, Ultisol (Bekenu Series). In this study, the seven treatments compared were: 14.88 g commercial fertilizer with grade 15 N:15 P:15K – zeolite (T1), 14.88 g mixed fertilizer with grade 15 N:15 P:15 K + zeolite (T2), 22.35 g mixed fertilizer with grade 10 N:10 P:10 K + zeolite (T3), 27.87 g mixed fertilizer with grade 8 N:8 P:8 K + zeolite (T4), 40.46 g mixed fertilizer with grade 5.5 N:5.5 P:5.5 K + zeolite (T5), 2.425 g urea without additives (T6) and soil only (T7). Standard procedures were used to evaluate these treatments. Treatments with zeolite significantly reduced NH3 loss compared with urea without addictives. They also improved retention of exchangeable NH4 + and NO3 - , and this was possible because zeolite favoured formation of NH4 + and NO3 - over NH3. T1, T2, T3, T4 and T5 reduced maximum of NH3 loss from 8.4 to 0.12, 5.16, 4.02, 4.5 and 3.41% (of the N added as urea), respectively. The maximum NH3 loss occurred on day 2 for T6, day 3 for T1, day 4 for T3 and day 5 for T2, T4 and T5 of incubation. Afterwards, there was a general decline until day 15 when the NH3 loss was about 1% of the N added as urea. T1 caused the highest accumulation of exchangeable NH4 + while T5 caused the highest accumulation of available NO3 -. These mixed fertilizers were further tested in a pot experiment where Masmadu maize (Zea mays L) was used as a test crop. The objectives of this study were to evaluate the effects of the treatments on: (1) Plant height, dry matter, N, P, and K uptake N, P, and K use efficiency and their production efficiency in maize cultivation, and (2) Soil exchangeable NH4 +, available NO3 - , pH, exchangeable K and available P contents. The treatments evaluated were: 14.88 g commercial fertilizer with grade 15 N:15 P:15K - zeolite (T1), 14.88 g mixed fertilizer with grade 15 N:15 P:15 K + zeolite (T2), 22.35 g mixed fertilizer with grade 10 N:10 P:10 K + zeolite (T3), 27.87 g mixed fertilizer with grade 8 N:8 P:8 K + zeolite (T4), 40.46 g mixed fertilizer with grade 5.5 N:5.5 P:5.5 K + zeolite (T5) and soil only (T7). The amounts of mixed fertilizer applied were based on the standard recommendation for mature Masmadu Maize. The effect of T1 and T5 on soil total N was significant compared with T7. Treatments with higher amounts of clinoptilolite zeolite (T4 and T5) significantly improved soil total P, K and available K compared to T1 and T7. T4 and T5 caused the highest accumulation of exchangeable NH4 + and available NO3 - compared to T1 and T7. T4 and T5 had a similar effect on plant height, dry matter, N, P and K concentrations, and uptake and use efficiency compared with T1. It may be concluded that treatments with higher amounts clinoptilolite zeolite, 27.87 g mixed fertilizer with grade 8 N:8 P:8 K + zeolite (T4), and 40.46 g mixed fertilizer with grade 5.5 N:5.5 P:5.5 K + zeolite (T5) ensured good retention of soil exchangeable cations within the Ultisol. However, field evaluation for the treatments for at least three cropping cycles, for corn yield (cob) and cost and benefits analysis are recommended as a further research for economic viability.